Sensing microgripper with pid control systems - Phan, Hữu Phú (Đại học Quốc gia Hà Nội, 2016)
Recently, MEMS and NANO are considered very importance technologies in 21th century that play a key role for the development of modern electronic devices. It was only in the early 90s of previous century that significant work in the field of micro-electro-mechanical systems (MEMS) began. At present, there is still a lack of tools for manipulation of microstructures that are not directly accessible by the existing machines or robots that handle macro objects. Therefore, the development of micro-tools for handling and manipulating particles or small components (sized in the micrometer range) with the applications envisioned in microassembly, microrobotics, single cell manipulation and positioning, cell separation, minimally invasive and living cell surgery continues to be a great technological challenge. The sensing microgripper is capable of providing large jaw displacement and output sensing voltage is presented in [4]. This device is able to monitor the jaw displacement and the resulting applied force. The device is made on SOI silicon wafers with a fabrication process compatible with CMOS technology. However, to commercialization this device, some additions research and development need to be continued such as reducing the operation temperature for living cell applications, improvement of accuracy in modeling, and its control system. This thesis will be focused in designing, and simulation a control system for the sensing microgripper based on a standard Bi-CMOS process. The target is built up a fully close-loop control manipulation system which is integrated on chip with the sensing microgripper.